2011
DOI: 10.3109/0886022x.2011.600495
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Clinical and Laboratory Presentations of Primary and Secondary Glomerular Diseases

Abstract: Objective: To investigate the clinicopathologic correlation of the glomerular diseases and to compare the presentations of primary and secondary glomerular diseases. Methods: Two hundred and sixty adult patients (men = 56.2%, mean age = 39.9 ± 16.0 years) who had undergone renal biopsy and been diagnosed with glomerular disease were retrospectively investigated. The information about the demographic and clinical characteristics of the patients, the indications for biopsy, the laboratory parameters, and the pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 16 publications
2
2
1
1
Order By: Relevance
“…Primary glomerulonephritis patients had higher median values of 24-hour urinary protein than lupus nephritis patients and this was similar to the results of a previous study (27). On contrary, another study did not nd statistically signi cant difference between primary GN and lupus nephritis as regard urinary protein levels (26).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Primary glomerulonephritis patients had higher median values of 24-hour urinary protein than lupus nephritis patients and this was similar to the results of a previous study (27). On contrary, another study did not nd statistically signi cant difference between primary GN and lupus nephritis as regard urinary protein levels (26).…”
Section: Discussionsupporting
confidence: 87%
“…In the present study, there were no statistically signi cant age and sex differences between primary glomerulonephritis and lupus nephritis patients. In agreement with this, two other studies reported similar results (26) (27). On contrary, marked female preponderance was noted for lupus nephritis and thin basement membrane nephropathy, whereas a modest male predominance was noted for acute postinfectious GN, FSGS and IgA nephropathy (28).…”
Section: Discussionsupporting
confidence: 82%
“…22 The worsening of renal function and the presence of hematuria were also related to secondary etiology in the final model of this study. In fact, Kutlugun et al 22 demonstrated that renal dysfunction (creatinine > 1.5 mg/dl) was significantly more related to SG.…”
Section: Discussionmentioning
confidence: 81%
“…On the other hand, Ferraz et al 7 and Kutlugun et al 22 found no gender differences among the etiologies. However, in the latter study there was a high prevalence of AA amyloidosis (43%) as a secondary cause, which may have been responsible for this difference in the results.…”
Section: Discussionmentioning
confidence: 92%
“…ХБП [1,2]. ГН подразделяются на первичные и вторичные [3]. Выделяют 4 варианта клинического течения первичного ГН -нефротический, гипертонический, смешанный и латентный.…”
unclassified